Differential Juvenile Hormone Variations in Scale Insect Extreme Sexual Dimorphism. - Isabelle Mifom Vea; Sayumi Tanaka; Takahiro Shiotsuki; Akiya Jouraku; Toshiharu Tanaka; Chieka Minakuchi (PLoS ONE, 2016)
Scale insects have evolved extreme sexual dimorphism, as demonstrated by sedentary juvenile-like females and ephemeral winged males. This dimorphism is established during the post-embryonic development; however, the underlying regulatory mechanisms have not yet been examined. We herein assessed the role of juvenile hormone (JH) on the diverging developmental pathways occurring in the male and female Japanese mealybug Planococcus kraunhiae (Kuwana). We provide, for the first time, detailed gene expression profiles related to JH signaling in scale insects. Prior to adult emergence, the transcript levels of JH acid O-methyltransferase, encoding a rate-limiting enzyme in JH biosynthesis, were higher in males than in females, suggesting that JH levels are higher in males. Furthermore, male quiescent pupal-like stages were associated with higher transcript levels of the JH receptor gene, Methoprene-tolerant and its co-activator taiman, as well as the JH early-response genes, Krüppel homolog 1 and broad. The exposure of male juveniles to an ectopic JH mimic prolonged the expression of Krüppel homolog 1 and broad, and delayed adult emergence by producing a supernumeral pupal stage. We propose that male wing development is first induced by up-regulated JH signaling compared to female expression pattern, but a decrease at the end of the prepupal stage is necessary for adult emergence, as evidenced by the JH mimic treatments. Furthermore, wing development seems linked to JH titers as JHM treatments on the pupal stage led to wing deformation. The female pedomorphic appearance was not reflected by the maintenance of high levels of JH. The results in this study suggest that differential variations in JH signaling may be responsible for sex-specific and radically different modes of metamorphosis.